(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This study investigates the effects of seed sowing rates and nitrogen fertilization on the yield components of chickpea varieties. The research focuses on the locally developed chickpea cultivars "Obod" and "Polvon". The findings enhance the understanding of how different agronomic practices influence the yield performance of these cultivars, providing valuable insights for optimizing chickpea production under local conditions.